2010
DOI: 10.1089/ten.tea.2009.0707
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Major Histocompatibility Complex-T Cell Receptor Signaling Allows Efficient Generation of Functional, Antigen-Specific CD8+T Cells from Embryonic Stem Cells and Thymic Progenitors

Abstract: Generation of early T cells by coculturing stem cells on notch-ligand-expressing OP9 stromal cells (OP9-DL1) has been widely reported. However, further differentiation of these cells into mature, antigen-specific, functional T cells, without retroviral transduction of T cell receptors (TcRs), is yet to be achieved. In the thymic niche this differentiation is controlled by the interaction of developing TcRs with major histocompatibility (MHC) molecules on stromal cells. We hypothesized that by providing exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…20 Furthermore, an in vitro model of TCR revision in mature human CD8+ T cells, induced by the presence of anti-CD3 and IL-7, was recently described. 43 In particular, IL-7 has been shown to induce T cell survival and facilitate chromatin remodeling at the TCR loci in developing, immature T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Furthermore, an in vitro model of TCR revision in mature human CD8+ T cells, induced by the presence of anti-CD3 and IL-7, was recently described. 43 In particular, IL-7 has been shown to induce T cell survival and facilitate chromatin remodeling at the TCR loci in developing, immature T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that treatment of mouse DP thymocytes with antigen-loaded H-2K b MHC class I tetramers, anti-CD28, anti-CD3, IL-2, and IL-7 results in RAG-1 upregulation, suggesting that TCR gene rearrangement is initiated or continued due to the presence of MHC tetramers [20]. Furthermore, an in vitro model of TCR revision in mature human CD81 T cells, induced by the presence of anti-CD3 and IL-7, was recently described [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the co-culture signaling responses governing cell specification can instruct synthetic platforms to recapitulate native responses; for example, the maturation of stem cells to produce antigen specific T cells has been accomplished by providing major histocompatibility complex molecules from either stromal cells or as tetramers in solution [31]. Additionally, patterning approaches have demonstrated the ability to create complex co-culture platforms, and thereby may inform approaches to spatially control differentiation.…”
Section: Stem Cell-derived Factor Manipulationmentioning
confidence: 99%
“…In these studies iPS cells were differentiated into the hematopoietic lineage by co-culturing with a bone marrow stromal cell line (OP9) or its derivatives (e.g. notch-ligand transfected OP9 cells, OP9-DL1), which has been well established to support ES cell hematopoiesis and to generate lymphoid lineages [15, 16]. Despite significant advances, ultimate clinical application requires therapeutic cells to be free of stromal cell contamination, which is difficult to achieve through cell sorting techniques.…”
Section: Introductionmentioning
confidence: 99%